2012
DOI: 10.1007/s12603-011-0079-4
|View full text |Cite
|
Sign up to set email alerts
|

Water homeostasis, frailty and cognitive function in the nursing home

Abstract: We proposed the ECW/TBW ratio and BIVA as surrogate methods for the clinical assessment of frailty. We tested successfully both approaches with nursing home patients and free-living volunteers and compared them to a national data base. The advent of new, portable instruments will enable field tests to further validate our proposed "Frailty Factor" in future studies. We found no correlation between frailty and cognitive decline in the nursing home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…In one approach, multiple dilution entails taking a predose blood or urine sample and then allowing a 3‐ to 5‐hour equilibration period following dosing with deuterium oxide and sodium bromide solutions (with longer periods for individuals with expanded ECW, including those with extreme obesity, particularly for ECW determination by bromide dilution 79 ) before a final postdose blood or urine sample is collected. Deuterium enrichment of the biological sample may be determined by isotope ratio mass spectrometry 80 ‐ 82 or Fourier transform infrared spectrometry, 83 and bromide enrichment can be determined by high‐performance liquid chromatography 84 , 85 or nondestructive liquid X‐ray fluorescence 86 . The reader is referred to the International Atomic Energy Agency website resources 87 and the excellent chapter by Schoeller 88 on this topic.…”
Section: Reference Methods For Lean Tissue Assessment In Clinical Resmentioning
confidence: 99%
“…In one approach, multiple dilution entails taking a predose blood or urine sample and then allowing a 3‐ to 5‐hour equilibration period following dosing with deuterium oxide and sodium bromide solutions (with longer periods for individuals with expanded ECW, including those with extreme obesity, particularly for ECW determination by bromide dilution 79 ) before a final postdose blood or urine sample is collected. Deuterium enrichment of the biological sample may be determined by isotope ratio mass spectrometry 80 ‐ 82 or Fourier transform infrared spectrometry, 83 and bromide enrichment can be determined by high‐performance liquid chromatography 84 , 85 or nondestructive liquid X‐ray fluorescence 86 . The reader is referred to the International Atomic Energy Agency website resources 87 and the excellent chapter by Schoeller 88 on this topic.…”
Section: Reference Methods For Lean Tissue Assessment In Clinical Resmentioning
confidence: 99%
“…Corrected bromide space was used as the proxy for ECW and calculated using the following formula: corrected bromide space ¼ Br dose/Br elevation in plasma  0.90  0.95  0.94, where 0.90 is the correction factor for nonextracellular distribution, 0.95 is the Donnan equilibrium factor and 0.94 is the correction for water content in plasma. 11…”
Section: Extracellular Watermentioning
confidence: 99%
“…We adopted a gold standard to measure the TBW, but not to measure the ECW. Analysis of sodium bromide could give a more detailed information on ECW/TBW, although previous study showed a good agreement between BIVA analysis and isotopes [10]. In addition, we measured TBW only at the end of the program, which did not allow us to discuss the changes.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the use of stable isotopes can identify cell mass integrity by monitoring the extracellular water/total body water (ECW/TBW) ratio. Water, labeled with deuterium, tritium or oxygen-18, has been used to measure TBW [10], and methods such as sodium bromide dilution have been employed to measure ECW [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation